Pemikiran Kritis dalam Rekrutmen Penyelenggara Pemilu Menggunakan Sistem online Perspektif Hukum Tata Negara - Ngimadudin, Ngimadudin; Supriadi, Supriadi (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
Critical thinking in the context of recruiting election organizers using online systems is an urgent topic in constitutional law studies. In the digital era, technological transformation has fundamentally changed the electoral landscape. This research aims to analyze the implications of constitutional law for the use of online systems in recruiting election organizers. This research uses qualitative research approach with a document analysis and literature study. Through a critical approach, this research explores aspects such as fairness, transparency and accountability in the online recruitment process. By considering the democratic principles underlying constitutional law, this research highlights the legal challenges that may arise along with the adoption of technology in the recruitment of election administrators. An in-depth analysis of applicable legal norms will be carried out to assess the effectiveness and sustainability of the online system in maintaining the integrity and legitimacy of the general election process. It is hoped that the results of this research will provide valuable insight for the formulation of legal policies that are more adaptive to technological developments in the context of holding elections.